HEAVY METALS AND NUTRIENTS REMOVAL FROM SEWAGE WATER USING WATER HYACINTH, EICHHORNIA CRASSIPES - Mol. S, Reena; Murugesanb, A. G. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Water pollution is a serious health problem and the amount of industrial and domestic waste increases continuously in recent times. Phytoremediation is one effective methods to remove heavy metals and nutrients from the wastewater by Eichhornia crassipes. In this study, macrophytes were surveyed from the contaminated freshwater system and characterized macrophytes for phytoremediation. A total of twelve macrophytes were identified from the coir contamination pond and Eichhornia crassipes significantly improved water quality than other macrophytes (p<0.01). Water hyacinth (Eichhornia crassipes) is a rapidly growing, free-floating aquatic macrophyte. It is capable of assimilating large quantities of heavy metals and nutrients. Experiments were conducted and the uptake of arsenic, cadmium, lead, copper and zinc from the aqueous medium for five different concentrations ranging from 5 mg/L to 25 mg/L was evaluated. The uptake of heavy metal was analyzed and the efficacy was determined every week. The selected macrophyte was healthy, young and acclimatized in sewage water. Results revealed that at a 10 mg/L concentration of heavy metals, the removal efficiency was greater and plant growth was normal. The heavy metal removal efficiency was checked for water hyacinth. The heavy metal removal efficiency was between 45 and 97%. Phytoremediation treatment of coir retting wastewater using E. crassipes showed decreased total dissolved solids, total suspended solids, sulphate, chloride, calcium, magnesium and iron level. E. crassipes treated coir retting wastewater showed decreased phenol levels. The mean initial phenol level was 450 ± 10.2 mg/L before treatment. The percentage removal of phenol was 58% after 10 days and the percentage of phenol removal increased after 20 days of treatment (92.88%) (p<0.001). It was concluded that by using macrophytes, heavy metals and nutrients could be effectively removed from waste water.